1990
DOI: 10.1038/clpt.1990.92
|View full text |Cite
|
Sign up to set email alerts
|

A model to detect interactions between roxithromycin and oral contraceptives

Abstract: Twenty-two healthy women participated in a study to determine whether roxithromycin (a new macrolide antibiotic agent) obtunds the activity of a triphasic oral contraceptive. The duration of the study was four menstrual cycles. Medication was given as follows: (1) cycle 1, no medication to demonstrate ovulation; (2) cycle 2, triphasic oral contraceptive daily to suppress ovulation; (3) cycle 3, triphasic oral contraceptive daily plus roxithromycin, 150 mg b.i.d.; and (4) cycle 4, triphasic oral contraceptive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Roxithromycin has been reported to interact with theophylline, leading to a small but statistically significant increase in the Cm~ and the AUC of theophylline (Houin et al 1992;Saint-Salvi et al 1987). However, it has no clinically significant interaction with cyclosporin, carbamazepine, oral contraceptives, ranitidine or warfarin (Billaud et al 1990;Meyer et al 1990;Paulsen et al 1988;Saint-Salvi et al 1987;Young et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Roxithromycin has been reported to interact with theophylline, leading to a small but statistically significant increase in the Cm~ and the AUC of theophylline (Houin et al 1992;Saint-Salvi et al 1987). However, it has no clinically significant interaction with cyclosporin, carbamazepine, oral contraceptives, ranitidine or warfarin (Billaud et al 1990;Meyer et al 1990;Paulsen et al 1988;Saint-Salvi et al 1987;Young et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Using the rifampicin studies to illustrate this, the two earlier studies both showed ovulation in some women, 4,5 whereas the two later studies showed no ovulation. 6,7 However, the two earlier studies gave rifampicin for longer (21 days or more) than the later two (10 and 14 days).…”
Section: Studies Assessing Ovulation Parametersmentioning
confidence: 99%
“…[63][64][65] Progestogen-only contraception. Evidence for reduced efficacy of POPs with rifampicin is obtained from one small prospective study of nine women using antitubercular treatment (rifampicin and ethambutol).…”
Section: Liver Enzyme-inducing Antibioticsmentioning
confidence: 99%